Occupational exposure to dust in open pit mining. A short review. - Maria Matos (2012)
A literature review concerning the scientific knowledge of all the key factors related to respirable crystalline silica dust exposure was conducted and a chronological evolution of the state-of-the-art knowledge that can respond to questions raised by the development of the work done in quarries and opencast mines is presented, based on bibliographic research. Findings assert that exposure to silica dust is the most frequent and dangerous hazard in open pit mining. Some aspects meet consensus amid authors: tasks and work equipment, areas surrounding the quarry, methods of sampling, relationship between the amount collected and the legal limits set (TLV) in each country. "Good practice" preventive strategies towards the protection of the exposed workers comprehend early knowledgeable recognition of the danger followed by application of technical means of exposure control. A review evidence concerns the link between exposure, by inhalation of dust containing crystalline silica, and its harmful effect to human health, often deadly (silicosis). Authors noted that other work-related factors associated to exposure to silica dust may potentiate other occupational diseases. Silicosis is a preventable occupational disease, but not curable, accounting for new cases of death even among young workers. Thus an effective mandatory control of exposure to crystalline silica in the workplace is therefore crucial.